An improved SOI trench LDMOST with double vertical high-k insulator pillars *Project supported by the National Natural Science Foundation of China (Nos. 51237001, 51607026) and the Fundamental Research Funds for the Central Universities (No. ZYGX2016J048). (September 2018) - Li, Huan; Huang, Haimeng; Chen, Xingbi
Abstract: An SOI trench LDMOST (TLDMOST) with ultra-low specific on-resistance ( R on, sp ) is proposed. It features double vertical high- k insulator pillars (H k 1 and H k 2 ) in the oxide trench, which are connected to the source electrode and drain electrode, respectively. Firstly, under reverse bias voltage, most electric displacement lines produced by the charges of the depleted drift region in the source side go through the H k 1, and thus the average electric field strength under the source can be enhanced. Secondly, two additional electric field peaks are induced by the H k 1, which further modulate the electric field in the drift region under the source. Thirdly, most electric displacement lines produced by the charges of the depleted drift region in the drain side enter into the H k 2 . This not only introduces one more electric field peak at the corner of the oxide trench around the H k 2, but also forms the enhanced vertical reduced surface field effect, which modulates the electric field in the drift region under the drain. With the effects of the two H k insulator pillars, the breakdown voltage (BV) and the drift region doping concentration are significantly improved. The simulation results indicate that compared with the oxide trench LDMOST (previous TLDMOST) with the same geometry, the proposed double H k TLDMOST enhances the BV by 86% and reduces the R on, sp by 88%.